CD68+, but not stabilin-1+ tumor associated macrophages in gaps of ductal tumor structures negatively correlate with the lymphatic metastasis in human breast cancer - Buldakov, Mikhail; Riabov, Vladimir; Yin, Shuiping; Kzhyshkowska, Julia (Immunobiology, 2017)
Tumor associated macrophages (TAM) support tumor growth and metastasis in several animal models of breast cancer, and TAM amount is predictive for efficient tumor growth and metastatic spread via blood circulation. However, limited information is available about intratumoral TAM heterogeneity and functional role of TAM subpopulations in tumor progression. The aim of our study was to examine correlation of TAM presence in various morphological segments of human breast cancer with clinical parameters. Thirty six female patients with nonspecific invasive breast cancer T1-4N0-3M0 were included in the study. Morphological examination was performed using Carl Zeiss Axio Lab.A1 and MiraxMidiZeiss. Immunohistochemical and immunofluorescence/confocal microcopy analysis was used to detect CD68 and stabilin-1 in 5 different tumor segments: (1) areas with soft fibrous stroma; (2) areas with coarse fibrous stroma; (3) areas of maximum stromal-and-parenchymal relationship; (4) parenchymal elements; (5) gaps of ductal tumor structures. The highest expression of CD68 was in areas with soft fibrous stroma or areas of maximum stromal-and-parenchymal relationship (79%). The lowest expression of CD68 was in areas with coarse fiber stroma (23%). Inverse correlation of tumor size and expression of CD68 in gaps of tubular tumor structures was found (R=−0.67; p=0.02). In case of the lymph node metastases the average score of CD68 expression in ductal gaps tumor structures was lower (1.4±0.5) compared to negative lymph nodes case (3.1±1.0; F=10.9; p=0.007). Confocal microscopy identified 3 phenotypes of TAM: CD68+/stabilin-1−; CD68+/stabilin-1+ (over 50%); and CD68−/stabilin-1+. However, expression of stabilin-1 did not correlate with lymph node metastasis. We concluded, that increased amount of CD68+TAM in gaps of ductal tumor structures is protective against metastatic spread in regional lymph nodes.